Market integration between cryptocurrency and technology indices - Walker, Evan (College of Accounting, 2025)
This study investigates the relationship between cryptocurrency and semiconductor/technology indices for the period 2018(Q2) to 2023(Q2). The relationship was explored through use of correlation, Johansen cointegration, and Granger pairwise causality testing. The findings are key for determining the diversification benefits of cryptocurrencies and further examining the direction of causal relationships. The correlation results indicated weak to moderate correlation between cryptocurrencies and equity indices. The findings indicated that cryptocurrencies are cointegrated among each other and a bilateral causal relationship is present. Cointegration was found between cryptocurrencies and the Philadelphia Stock Exchange Semiconductor index, NASDAQ, S&P500, and Dow Jones. The NASDAQ, S&P500 and Dow Jones were found to cause crypto prices movements, but the reverse was true – for the latter two – when Binance was removed from the index. These findings suggest a lack of diversification benefits of cryptocurrencies compared to the semiconductor/technology sector. Investors should be careful when including cryptocurrencies into their portfolios as to not overexpose themselves to risk pervasive in both markets.